Provision of non-invasive coronary and carotid vascular imaging results on changes in diet and physical activity in asymptomatic adults: A scoping review - Radavelli-Bagatini, Simone; Gebre, Abadi K.; Kennedy, Mary A.; Sim, Marc; Blekkenhorst, Lauren C.; Bondonno, Catherine P.; Jackson, Ben; Dimmock, James; Schlaich, Markus P.; Hodgson, Jonathan M.; Lewis, Joshua R. (Frontiers in Nutrition, 2022)
Background: Although a healthy diet and physical activity have been shown to prevent or delay cardiovascular disease (CVD) hospitalizations and deaths, most adults do not meet current guidelines. Provision of coronary artery calcification (CAC) and carotid ultrasound (CUS) imaging results may motivate beneficial lifestyle changes. We scoped the existing literature for studies providing non-invasive vascular imaging results and reporting diet, physical activity, and/or anthropometric measures to identify knowledge gaps and opportunities for further research. Methods: A systematic search was performed across three electronic databases, in line with PRISMA ScR guidelines and Arksey and O'Malley’s scoping review framework. Results: Twenty studies (thirteen observational and seven randomized controlled trials) examining the impact of provision of CAC/CUS imaging results on diet and/or physical activity behaviors were included. Nearly half the studies did not clearly state whether participants received dietary and physical activity advice (n=7) along with vascular imaging results, and these were secondary outcomes in most studies, with data assessment and reporting being inconsistent. Conclusion: Well-designed clinical trials with consistent and clear messaging based on detailed subjective and objective measures of diet and physical activity are needed to determine whether this approach may stimulate long-term dietary and physical activity change. Keywords: Coronary artery calcification (CAC), carotid ultrasound (CUS), vascular imagining, cardiovascular disease (CVD), diet and physical activity change.